Intraoperative Management of Large Resuscitation-Associated Venous Air Embolism (VAE) for Emergent Neurological Surgery - Ryan S. D’Souza; Arnoley S. Abcejo; Matthew A. Sexton (Case Reports in Anesthesiology)
Venous air embolism (VAE) is a well-described phenomenon that may have life-threatening cardiopulmonary and neurological consequences. Accidental administration of air during resuscitation while using a rapid infuser is rare. Furthermore, there is a paucity of published data describing the intraoperative management of VAE during emergent nonseated neurological surgery. We report a 22-year-old previously healthy female who experienced a motor vehicle accident with severe facial and head trauma, and mixed subdural and epidural hematomas with an 8 mm midline shift. Computed tomography revealed significant air entrainment in the right heart and main pulmonary artery, with venous air tracking from the right axillary vein. Given her age, lack of preexisting cardiac comorbidities, hemodynamic stability, and critical cerebral herniation risk, further cardiac evaluation was deferred, and the patient was transferred to the operating room for emergent decompressive craniotomy. Intraoperatively, she experienced acute decrease in mean arterial pressure and end-expiratory carbon-dioxide with loss of pulse oximetry waveform concerning for obstructive VAE physiology. She was responsive to fluid resuscitation and epinephrine administration and did not experience any recurrence of obstructive VAE. This challenging case report describes positive neurologic and hemodynamic outcomes after resuscitation-associated VAE and cardiopulmonary collapse during emergency neurosurgery. Comprehensive evaluation of risk, urgency of procedure, and need for diagnostic monitoring and treatment should be personalized.